'(Dis)empowered by what we see … ': exploring the use of video-stimulated reflection in physical education pedagogy and practice. Issue 3 (2nd September 2017) - Mooney, Amanda; Hickey, Chris
ABSTRACT: Reflexive accounts of physical education (PE) pedagogy and practice offer potential to reveal much about the intended and unintended learning, for both students and teachers, that can result from certain pedagogic encounters. Despite the promotion of reflective practice/s as a possible 'panacea' for improved teaching and learning, there is widespread concern that such approaches have relatively little influence in 'shaking or stirring' the deep-seated notions of effective pedagogy that are held by many physical educators [Mordal-Moen, K., & Green, K. (2014). Neither shaking nor stirring: A case study of reflexivity in Norwegian PE teacher education. Sport, Education and Society, 19 (4), 415–434]. Inherent here are concerns that an increase in critical awareness alone does not necessarily lead to pedagogic translation [Hickey, C. (2001). "I feel enlightened now, but … ": The limits to the pedagogic translation of critical social discourses in PE. Journal of Teaching in Physical Education, 20 (3), 227–246]. Against that backdrop, we continue to support the use of reflective practice techniques as tools through which to interrogate the socio-cultural conditions and power relations that install enduring notions of effective pedagogy and dominant professional identities [Coia, L., & Taylor, M. (2017). Let's stay in the swamp: Poststructural feminist reflective practice. In R. Brandenburg, K. Glasswell, M. Jones, & J. Ryan (Eds.), Reflective theory and practice in teacher education (pp. 49–62). Singapore: Springer Singapore]. In this paper, we explore PE pedagogy and practice through reflective practice with two female teachers in all-boys' schools. Specifically, we critique the use of video-stimulated reflections from a feminist poststructuralist perspective to make visible the possibilities, challenges and tensions inherent in this methodological approach.